A Novel One‐Pot Sulfonyloxylactonization of Alkenoic Acids Mediated by Hypervalent Iodine Species Generated in situ from Ammonium Iodide. Issue 1 (January 2014) - Hu, Jiantao; Zhu, Min; Xu, Yuan; Yan, Jie
Abstract A novel and efficient one‐pot procedure was designed for the sulfonyloxylactonization of alkenoic acids by the reaction of alkenoic acids with m‐chloroperbenzoic acid and sulfonic acids in the presence of a catalytic amount of ammonium iodide in a mixture acetonitrile/2, 2, 2‐trifluoroethanol (4 : 1) at room temperature for 24 h, which provided the corresponding sulfonyloxy lactones in moderate‐to‐good yields.